Genome-Wide Analysis of WRKY Genes and Their Response to Hormone and Mechanic Stresses in Carrot - Nan, Hong; Gao, Li-zhi (Frontiers in Genetics, 2019)
The WRKY gene family plays a vital role in plant development and environment response. Although previous studies suggested that the WRKY genes in carrot (Kuroda type) involved in biotic and abiotic stress responses, the information of WRKY genes in the latest version of the carrot genome (Daucus carota v2.0, Nantes type carrot) and their response to hormone and injury stresses have not been reported. In this study, we performed a genome-wide analysis of WRKYs using a chromosome-scale genome assembly of carrot (Daucus carota subsp. sativus L.). We identified a total of 67 WRKY genes, which were further classified into the three groups. These WRKY genes are unevenly distributed on carrot chromosomes. We found that more than half of them were derived from whole-genome duplication (WGD) events, suggesting that WGDs have played a major role during the evolution of the WRKY gene family. We experimentally ascertained the expression divergence existed between WGD-derived WRKY duplicated gene pairs, which is indicative of functional differentiation between duplicated genes. Our analysis of cis-acting elements indicated that WRKY genes were transcriptionally regulated upon hormone and mechanic injury stresses. Gene expression analyses by qRT-PCR further presented that WRKY genes were involved in hormone and mechanic injury stresses.